Thyroid status and Treatment Response of Hypothyroid Infertile Women in Tertiary Care Center of Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective(s): Aim of this study was to find out the prevalence of hypothyroidism in infertile women as well as to assess their response to treatment.Materials and methods: This descriptive study was conducted in Infertility unit of Department of Obstetrics and Gynecology, Bangabandhu Sheikh Mujib Medical University, Bangladesh, a tertiary care centre from January 2014 to December 2014. Four hundred women who visited infertility clinic of the department for fertility treatment were the target population for this study. Routine investigations such as CBC, Blood sugar 2 hours postparandial or GTT, TSH and Prolactin was done. Subclinical hypothyroidism was diagnosed when there was increased TSH and normal FT4. Hypothyroid patients were given Levothyroxin depending upon TSH levels and continued until end of the study. Patients were followed up for six months even if pregnancy was attained.Results: Out of 400 women 55% were primary and 45% were secondary subfertility. Mean duration of infertility was 4.5 ± 1.2 years. Ninety two (23%) patients were hypothyroid. Among them 66 (16.5%) were subclinical hypothyroid and 26 (6.5%) were frank hypothyroid. The mean TSH levels were 7.34 ± 2.13 ìIU/ml, and the mean PRL levels were 52.46 ± 11.17 ng/ml. Out of 92 infertile women diagnosed as hypothyroidism 75 (81.52%) women conceived after treatment with drugs for hypothyroidism (dose depending upon severity of hypothyroidism, i.e. TSH levels). More than 90% women had regular ovulation for consecutive three cycles after initiation of treatment.Conclusion: The normal TSH levels are the pre-requisite for fertilization. The decision to initiate thyroid replacement therapy in both clinical and subclinical hypothyroidism at early stage is justified in infertile women.Bangladesh J Obstet Gynaecol, 2016; Vol. 31(2) : 86-89